Measurement of uranium and radon concentration in drinking water samples and assessment of ingestion dose to local population in Jalandhar district of Punjab, India. Issue 5 (June 2019) - Kumar, Manish; Kaushal, Anjali; Sahoo, B. K.; Sarin, Amit; Mehra, Rohit; Jakhu, Rajan; Bhalla, Atul; Sharma, Navjeet
A study was conducted to assess the concentration of uranium and dissolved radon in drinking water samples collected from Jalandhar district of Punjab, India. The samples were analysed for dissolved radon using scintillation cell method. Laser fluorimetry was used for measurement of uranium concentration. Correlation analysis of radon and uranium concentrations and salinity and total dissolved solids with uranium was carried out. The uranium concentration in water samples varied from a minimum value of 1.53 ± 0.06 mg m −3 to 50.2 ± 0.08 mg m −3 with a geometric mean value of 14.85 mg m −3 . The radon concentration in water varied from a minimum value of 0.34 ± 0.07 kBq m −3 to a maximum value of 3.84 ± 0.48 kBq m −3 with a geometric mean value of 1.46 kBq m −3 . Ingestion dose to local population, due to radon and uranium in drinking water, for different age categories, was computed and results are being reported in this paper.